Pigeon math - Citro, Asia (Innovation Press, 2019)
Telling a story about pigeons should be simple. But what's a narrator to do when the number of feathered friends is constantly changing? Can our intrepid storyteller use math facts to keep up with the unstable quantities...or is this pigeon-centric tale doomed?